Modeling And Simulation Of Reactive Distillation Column For The Production Of Methyltertiary Butyl Ether (MTBE) Incorporating Structured Or Random Packing - Chan, Hui Yee (Universiti Sains Malaysia, 2018)
A simulation of reactive distillation column has been developed for the production of methyl tertiary butyl ether (MTBE). The proposed model was validated by comparing the simulated results obtained from Aspen Plus with the simulation data from the literature. The temperature and composition profiles obtained from simulations showed close agreement with the literature reported data. The simulation basis of reactive distillation column was set. It is assumed that the reactive distillation column has a total number of 17 stages. The reactive distillation column has two feed streams, which is a methanol feed on stage 3 and a mixed butenes feed on stage 11. The column pressure used is 11atm. The reflux ratio is 7. With the optimised column configuration and operating conditions, an isobutene conversion up to 99.9 was obtained through simulation. There are 26 different structured and random packings available in Aspen Plus V8.8 are selected in this research. 13 different structured packings and 13 different random packings are simulated by using simulation basis proposed. The packing section of MTBE synthesis set from stage 4 as starting stage and stage 11 as ending stage. The height equivalent of a theoretical plate (HETP), pressure drop and liquid holdup has been determined for different catalytic packing. Simulation results for MTBE synthesis are compared with optimised results that cover the isobutene conversion and MTBE purity.